'Anarchism, pure and simple': M. P. T. Acharya, anti-colonialism and the international anarchist movement. Issue 2 (2nd April 2020) - Laursen, Ole Birk
ABSTRACT: In late 1922, the Indian revolutionary M. P. T. Acharya returned to Berlin from Moscow and joined the international anarchist movement. Straddling anti-colonial, anarchist, and pacifist circles in the interwar years, Acharya stands out as a distinctive figure within global revolutionary networks and broadens our conception of the global reach of the international anarchist movement. Staking out a different path towards freedom than most of his contemporaries, an analysis of Acharya's activities within the international anarchist movement enables a more nuanced understanding of anti-colonial struggles against the totalised oppression of the state and redirects our attention towards anarchist conceptions of non-statist national liberation movements within anti-colonial frameworks. In doing so, the article extends recent scholarship on anarchism in the colonial and postcolonial world but also acknowledges anarchism's limitations. However, exploring Acharya's life and thought is part of a greater ambition to consider post-independent Indian politics through anarchism – a rejection of the nation-state as a necessity for nation liberation – as well as to allow for anti-authoritarian voices within India's freedom struggle to be heard alongside a polyphony of independence narratives.